American Society for Enhanced Recovery and Perioperative Quality Initiative Joint Consensus Statement on Perioperative Management of Patients on Preoperative Opioid Therapy. (August 2019) - Edwards, David A.; Hedrick, Traci L.; Jayaram, Jennifer; Argoff, Charles; Gulur, Padma; Holubar, Stefan D.; Gan, Tong J.; Mythen, Michael G.; Miller, Timothy E.; Shaw, Andrew D.; Thacker, Julie K. M.; McEvoy, Matthew D.; et al.
Abstract : Enhanced recovery pathways have quickly become part of the standard of care for patients undergoing elective surgery, especially in North America and Europe. One of the central tenets of this multidisciplinary approach is the use of multimodal analgesia with opioid-sparing and even opioid-free anesthesia and analgesia. However, the current state is a historically high use of opioids for both appropriate and inappropriate reasons, and patients with chronic opioid use before their surgery represent a common, often difficult-to-manage population for the enhanced recovery providers and health care team at large. Furthermore, limited evidence and few proven successful protocols exist to guide providers caring for these at-risk patients throughout their elective surgical experience. Therefore, the fourth Perioperative Quality Initiative brought together an international team of multidisciplinary experts, including anesthesiologists, nurse anesthetists, surgeons, pain specialists, neurologists, nurses, and other experts with the objective of providing consensus recommendations. Specifically, the goal of this consensus document is to minimize opioid-related complications by providing expert-based consensus recommendations that reflect the strength of the medical evidence regarding: (1) the definition, categorization, and risk stratification of patients receiving opioids before surgery; (2) optimal perioperative treatment strategies for patients receiving preoperative opioids; and (3) optimal discharge and continuity of care management practices for patients receiving opioids preoperatively. The overarching theme of this document is to provide health care providers with guidance to reduce potentially avoidable opioid-related complications including opioid dependence (both physical and behavioral), disability, and death. Enhanced recovery programs attempt to incorporate best practices into pathways of care. By presenting the available evidence for perioperative management of patients on opioids, this consensus panel hopes to encourage further development of pathways specific to this high-risk group to mitigate the often unintentional iatrogenic and untoward effects of opioids and to improve perioperative outcomes.